Green construction in building renovation = Zielone budownictwo w renowacji budynków - Ksit, Barbara; Majcherek, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Modern materials and construction solutions draw more and more attention to ecology and building certification. Among the criteria appearing in revitalization, an important element is bringing plants back into heavily urbanized areas. In its natural form, this is not possible to carry out everywhere, often requiring large amounts of space. Nowadays, however, there are a number of green roofs and green wall systems, allowing "greener" construction without making significant changes in the urban environment.
Keywords: zielone budownictwo; rewitalizacja; dachy zielone; ściany zielone; budownictwo zrównoważone; green buildings; revitalisation; green roofs; green walls; sustainable buildings